Love as Portrayed in the Satellite Music Video by Harry Styles: A Multimodal Analysis - Rahma Naza Shakila; Ernie D. A. Imperiani (Passage: Journal of English Language and Literature, 2024)
This study aims to investigate the love portrayal through the use of multimodality in Satellite music video by Harry Styles. The data were taken from Satellite music video by Harry Styles, which was published on YouTube. The study used a descriptive-qualitative method to analyze the data. Several theories were used in analyzing the data, including the multimodality theory by Anstey and Bull (2010) and the visual grammar theory by Kress and Leeuwen (2006) to identify the modes used in the music video. The triangular theory of love by Sternberg (1986, 1997) was also used to identify the kinds of love portrayed in the music video. Based on the analysis, it was found that the Satellite music video uses only four of the five modes, such as Linguistic, Visual, Gestural, and Spatial. Despite the audio mode being excluded, these four modes effectively communicate and convey the key message, which is the love portrayal. The Satellite music video portrayed the stages of unrequited love, employing three kinds of love, namely Nonlove, Liking, and Empty Love. Meanwhile, other kinds of love that are not portrayed are Infatuated Love, Romantic Love, Companionate Love, Fatuous Love, and Consummate Love. Therefore, it suggested for further study to analyze the additional layers of meaning which can be achieved by using the complete five modes and looking into personal life background.